Health status and living conditions of families ascribed to the Family Health Units - de Oliveira Sato, Tatiana; Driusso, Patricia; Vitale Torkomian Joaquim, Regina Helena; Simões Matsukura, Thelma; Cangiani Fabbro, Marcia Regina; Garcia de Oliveira Duarte, Ana Cláudia; Silvia Moccellin, Ana; Salvini, Tania de Fátima; Zem-Mascarenhas, Silvia Helena (O Mundo da Saúde, 2015)
The Health System is seeking to redirect the attention model, with the focus on programs and services centered on curative and hospital care for care focused on health needs, with emphasis on health promotion and diseases prevention. In this context, the Primary Health Care appears as the gateway to the needs and health problems of the population, making it important to know the demographic and epidemiological profile for the development of their actions. The aim of this study was to characterize the living conditions and health of the population assigned to the Family Health Units in São Carlos / SP. The study was conducted with 2407 families from 16 Family Health Units. We used a standardized form. Interviews were conducted with the person responsible for the household present at the time of the survey. Data were entered into Epi Info and descriptively analyzed. Regarding schooling 41.1% has incomplete primary education. The houses are mostly of their own (76.2%), have water supply (98.4%), sewage (97.5%) and garbage collection (92.1%). The most common health problems were hypertension (10.5%), altera- tions in musculoskeletal system (6.8%) and respiratory system (5.7%). The most cited health needs were dental care (12.8%), clinical investigation (12.7%) and physical activity (9.9%). From this survey it was possible to determine the demographic and epidemiological profiles of the population. The most common health problems are non-communicable chronic diseases.